Connecting Social Work and Activism in the Arts Through Continuing Professional Education. Issue 4 (7th August 2016) - Rawdon, Kathryn; Moxley, David
ABSTRACT: The authors place a continuing education conference devoted to linking the arts, social practice, and social work within the context of a movement to advance arts activism. They illustrate how social workers, artists, and community arts activists can collaborate in building public awareness about serious social issues, creating alternative explanations of the causes of those issues, and producing opportunity structures for people experiencing social marginalization. By connecting arts activism and social work through the use of common values pertaining to social justice, social workers can engage the arts as a vehicle for social betterment.